Hello again!
We have this equation
x³ - 4x² + 2x + 10 = x² - 5x - 3
All we have to do is follow the steps that we know and remember, when you are doing Algebra make you used the easiest away. You can repeat the same steps over and over as long your answer is correct.
OMG I talked too much!
Ok let's solve this
x³ - 4x² + 2x + 10 = x² - 5x - 3
x³ - 4x² + 2x + 10 -x² -5x - 3 = 0
Now again, all we have to do is factorize. Be very careful when you are factorizing.
(x +1)(x² - 6x + 13) = 0
Set factors equal to 0
x + 1= 0 or x² - 6x + 13 = 0
x = -1
This is the answer!
Wait !
I didn't solve x² - 6x + 13 = 0 but I already know I will ended up having NO REAL SOLUTION!
I hope this help again!
A+ Guaranteed! Feel free to comment or message me if you have further questions about the answer.
Peace :)